Romance during the Revolution In Surabaya and Its Surrounding Areas - Kasuma, Gayung (MOZAIK HUMANIORA, 2024)
This article discusses the romantic aspects of social life during revolutionary period in the city of Surabaya and its surroundings. After the battle of November 1945, the term "police action" became very popular when the Dutch in 1947 and 1948 carried out various acts of physical violence. This action has been a pivotal part of the revolution and the collective memory of the Surabaya people. While such incident occurred, several cities in East Java also became refugee areas and guerrilla bases for militias and fighters, including Mojokerto and Malang, as well as other cities. It cannot be denied that the people of these regions were also involved in this upheaval. During the revolution there were cases that had not been revealed regarding sexual matters. On the other hand, the lives of soldiers and warriors are also related to matters of romance, love, and marriage, which are of special record in times of war, emergency or normal. War and sexuality are inseparable parts of the revolutionary struggle, and the lives of soldiers involved in conflict. Various incidents related to sex, turmoil and tension have occurred in East Java in general and Surabaya in particular. In addition, civilian victims and prisoners are evidence of systematic acts of violence carried out by both sides.